Digital transformation and student satisfaction at the Autonomous University of Chile - Muñoz Acuña, Javier Manuel; Hernández-Perlines, Felipe; Ibarra Cisneros, Manuel Alejandro (Journal of Management and Business Education, 2024)
The great advances that derive from the technological revolution 4.0 have permeated higher education institutions, which have been forced to initiate extensive transformation processes that consider the integration of digital technologies to guarantee student satisfaction, maintain their social validity and ensure their sustainability. In this article, focused on the case of the Autonomous University of Chile, the existence of causal relationships between the Digital Transformation model of that University and the Student Satisfaction Index model proposed by Turkyilmaz, Temizer and Oztekin (2018) is demonstrated. The objective of the research was to determine the impact of the digital transformation on the student’s satisfaction of that University. The structural equation modeling technique was applied, using the data obtained from a questionnaire applied to 313 students at that University in the month of May 2023. The analyzes carried out empirically validated the proposed theoretical model, demonstrating that perceived quality is the variable that has the greatest effect on student satisfaction, and finding that the expectations created regarding the results of the digital transformation of the University have a negative influence on the satisfaction; In other words, the higher the expectations about digital transformation, the more difficult it will be to satisfy students and achieve their loyalty to the institution.